Continuous versus intermittent intraoperative neuromonitoring in complex benign thyroid surgery: A retrospective analysis and prospective follow‐up. (8th October 2019) - Sedlmaier, Anke; Steinmüller, Thomas; Hermanns, Mechthild; Nawka, Tadeus; Weikert, Sebastian; Sedlmaier, Benedikt; Caffier, Philipp P.
Abstract: Objectives: To compare continuous (C‐IONM) vs intermittent intraoperative neuromonitoring (I‐IONM) in complex benign thyroid surgery, and to follow up patients with loss of signal (LOS) or unilateral vocal fold paralysis (UVFP). Design: Retrospective clinical study, prospective case series. Setting: University hospital and academic teaching hospital of Charité—University Medicine Berlin, Germany. Participants: C‐IONM‐ and I‐IONM‐assisted thyroid surgery was conducted in 357 patients diagnosed with recurrent goitre, Graves' disease, complex hyperparathyroidism, cervical preoperation (anterior access) and LOS in primary operation (2‐stage thyroidectomy). Main outcome measures: To evaluate the incidence of early postoperative and permanent UVFP, and to report the results of phonosurgical therapy in patients suffering from persisting dysphonia. Results: In 346 patients enrolled (81.8% female, 18.2% male) with 613 nerves at risk (NAR) being monitored (409 I‐IONM vs 204 C‐IONM), early postoperative UVFP was observed in 10.5% of I‐IONM vs 4.9% of C‐IONM group ( P  < .05), permanent paralysis in 1.5% of I‐IONM vs 1.0% of C‐IONM group ( P  = .619). In total, 72 patients (21%) experienced pathological events (19 LOS < 100 μV, 53 transient or permanent UVFP). Three patients with permanent UVFP and persisting dysphonia received phonosurgery with stable improvements of all acoustic‐aerodynamic parameters. Conclusion: Compared to I‐IONM, C‐IONM‐application in complex benign thyroid surgery shows a significant reduction of transient UVFP and a non‐significant trend in preventing permanent UVFP. In persistent UVFP with dysphonia, endolaryngeal phonomicrosurgery and transcervical laryngeal framework surgery are long‐term effective treatment approaches to improve vocal function.